Forage Grasses for Florida's Organic Soils - Ikechukwu V. Ezenwa; Rosa M. Muchovej; Findlay M. Pate (EDIS, 2009)
Revised! SS-AGR-71, a 3-page fact sheet by I. V. Ezenwa, R. M. Muchovej, and F. M. Pate, is part of the Florida Forage Handbook. It highlights the two forage grasses recommended for the fertile organic soils of the Everglades Agricultural Area (EAA) — St. Augustinegrass and Limpograss. Includes references. Published by the UF Department of Agronomy, March 2009.